Pengaruh Promosi dan Harga Terhadap Keputusan Pembelian Motor Honda Scoopy di Dealer Wahana Cisoka Kabupaten Tangerang - Cahyono, Yoyok; Suryani, Popong; Januari Yanti, Ati (JOURNAL INTELEKTUAL, 2023)
Introduction/Main Objectives: To analyze and determine the influence of Promotion and Price capabilities on the decision to purchase a Honda Scoopy motorbike at a Cisoka vehicle dealer. Background Problems: Manufacturers are competing to create quality products and create new innovations in order to attract consumer interest and to be able to win a market competition based on consumers in choosing a product, especially motorcycles. Novelty: Re-testing on the same variables by previous researchers, with different research objects and subjects. Research Methods: The technique used in sampling in this study was purposive sampling. In this study, data analysis used SPSS version 23. Finding/Results: There is an influence of Promotion and Price on the decision to purchase a Honda Scoopy motorbike at the Cisoka vehicle dealer with a percentage of 77.6%. Conclusion: Policy making on purchasing decisions can be seen from competitive prices with competitors that must be considered and promotions through various media, both online and offline.